1997
DOI: 10.2134/agronj1997.00021962008900060008x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effect on Soil Water Content and Corn Yield in a Strip Intercropping System

Abstract: A three‐crop strip intercropping system including corn (Zea mays L.), soybean [Glycine max (L.) Merr.], and oat (Avena sativa L.) interseeded with nondormant alfalfa (Medicago sativa L.), was established in south‐central Iowa on a poorly drained Haig soil (fine, smectitic, mesic Vertic Argiaquoll). In 1989 (a dry year) and 1990 (a wet year), we studied the effect of tillage treatment (conventional, CT; reduced, RT; and no‐till, NT) and row position on soil water content, canopy and air temperatures, corn grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
1
15
0
3
Order By: Relevance
“…Plants of row 1 generated a second ear in 60% of the time of plants of row 1 and plants of row 12 generated a second ear 40% of the time (Table 3). Similar results were reported by Lesoing and Francis [20] and Ghaffarzadeh et al [26].…”
Section: Grain Yield Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…Plants of row 1 generated a second ear in 60% of the time of plants of row 1 and plants of row 12 generated a second ear 40% of the time (Table 3). Similar results were reported by Lesoing and Francis [20] and Ghaffarzadeh et al [26].…”
Section: Grain Yield Componentssupporting
confidence: 91%
“…Previous experiments report contrasting responses on the water stress on this yield component [20,21,26,28,29]. It is important to note that two weeks following crop blooming, the young grain does not accumulate dry weight.…”
Section: Treatmentmentioning
confidence: 95%
“…Although significant at only two of six site years, higher plant populations in our border rows were associated with higher yields. Ghaffarzadeh et al (1997) found more ears per plant, more kernels per ear, and higher seed weight from corn in border rows next to soybean than in the inside rows of the corn strips. West and Griffith (1992) found higher yields for intercropped corn at higher populations than in solid‐seeded rows.…”
Section: Resultsmentioning
confidence: 85%
“…Yang et al (2010) found out that grain yield and N uptake of maize in intercrop were significantly greater than those of sole maize and grain yield of soybean as an intercrop which is significantly lower than sole soybean and their N uptake relatively, thus indicating that intercropping favoured nutrient uptake and growth of maize and the growth of soybean significantly. According to Ghaffarzadeh et al (1997), the basic ideas are based on how different species interact during intercropping competition for resources which arise from varying time of planting, root growth patterns and different resource demands. At high levels of N, under intercropping, Ezumah et al (1987) and Ofori and Stern (1987) observed that grain and legume yield was reduced by the maize intercrop.…”
Section: Contributions Of Intercropping To the Soil Growth And Yieldmentioning
confidence: 99%